2007
DOI: 10.1111/j.1365-294x.2006.03168.x
|View full text |Cite
|
Sign up to set email alerts
|

Broad‐ to fine‐scale population genetic patterning in the smallmouth bassMicropterus dolomieuacross the Laurentian Great Lakes and beyond: an interplay of behaviour and geography

Abstract: Analysis of population genetic relationships reveals the signatures of current processes such as spawning behaviour and migration, as well as those of historical events including vicariance and climate change. This study examines these signatures through testing broad- to fine-scale genetic patterns among smallmouth bass Micropterus dolomieu spawning populations across their native Great Lakes range and outgroup areas, with fine-scale concentration in Lake Erie. Our primary hypotheses include whether genetic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
98
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(109 citation statements)
references
References 69 publications
11
98
0
Order By: Relevance
“…This may be due to the nature of our coastal sampling sites: many of these shallow nearshore areas would freeze over in winter and be less accessible, thus promoting an annual recolonization of sites. Also, some coastal fishes show high nest fidelity and can have substantial genetic divergence within the same lake, despite the absence of geographic barriers (Stepien et al 2007), which implies that dispersal may be limiting for some coastal species. Although we might expect that small-bodied species are possibly more dispersal limited because of a lower mobility and smaller home range size, the ratio of abundance of small-bodied to large-bodied fishes was not related to the amount of independent spatial variation explained (R 2 = 0.10).…”
Section: Traitsmentioning
confidence: 99%
“…This may be due to the nature of our coastal sampling sites: many of these shallow nearshore areas would freeze over in winter and be less accessible, thus promoting an annual recolonization of sites. Also, some coastal fishes show high nest fidelity and can have substantial genetic divergence within the same lake, despite the absence of geographic barriers (Stepien et al 2007), which implies that dispersal may be limiting for some coastal species. Although we might expect that small-bodied species are possibly more dispersal limited because of a lower mobility and smaller home range size, the ratio of abundance of small-bodied to large-bodied fishes was not related to the amount of independent spatial variation explained (R 2 = 0.10).…”
Section: Traitsmentioning
confidence: 99%
“…A Lake Erie smallmouth bass genetics study showed that migration rates may be higher in lake-spawning, as opposed to lotic-spawning, smallmouth bass (Stepien et al, 2007). Findings from this study and other evidence from Lake Erie (Stepien et al, 2007) may indicate that this population is more "open", with some individuals leaving the Archipelago. Therefore, northern Lake Michigan may need to be considered one management unit for smallmouth bass.…”
Section: Discussionmentioning
confidence: 49%
“…If this structure is a consequence of high-level population differentiation, which may be caused for example by a long-term historical divergence (i.e., the species was subdivided), then a multivariate analysis of genetic divergence will show distinct population clusters with no clear pattern of variation among the waterheads within these clusters. This alternative again relies on supporting prediction 1.2 at the ''correct'' hierarchical level within the same reproductive units (e.g., Telles and Diniz-Filho 2005; see also Stepien et al 2007). If this pattern of long-term differentiation is known a priori and these regions can be inferred independently such as from ecological or limnological data, then the magnitude of genetic variation that can be attributed to each of these levels can be measured by a hierarchical model such as nested ANOVA.…”
Section: Genetic Comparisons Among Samples From Distinct Waterheadsmentioning
confidence: 98%
“…1.1 Under homing behavior, a high genetic variability is expected to exist among waterheads because individuals reproducing within each one will tend to mate successively within a subsample of the total population (e.g., Stepien and Faber 1998;Waters et al 2000;Exadactylos et al 2003;Hoffman et al 2005;Stepien et al 2007;Pereira et al 2009;Abreu et al 2009;Waldman et al 2008 andGoodman et al 2008 for an inverted reasoning using this type of data-i.e., low levels of population differentiation is indicative of the absence of strong homing behavior). Likewise, kinship (i.e., co-ancestry) among individuals within waterheads will be higher than among individuals belonging to different waterheads.…”
Section: Genetic Comparisons Among Samples From Distinct Waterheadsmentioning
confidence: 99%